Money and credit : their influence on jobs, prices, and growth - Commission on money and credit (Englewood Cliffs, 1961)
The Commission on Money and Credit was es tablished by the unanimous vote of the Board of Trustees of the Committee for Economic Develop ment. The by-laws governing the Commission on Money and Credit state that "it shall be the respon sibility of the Commission to initiate studies into the United States monetary and financial system. All re search is to be thoroughly objective in character and the approach in each instance is to be from the stand point of the general welfare and not from that of any special political or economic group." The Commis sion, however, "shall fix its own rules and determine the scope of its studies." Publication of this report does not necessarily constitute endorsement of the recommendations presented in the Report by the Commission's advisory board, its research staff, or any member of any board or committee (other than the Commission) or any officer, of the Committee for Economic Development or any other organization participating in the work of the Commission.